2021
DOI: 10.3390/diagnostics11061081
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review and Meta-Analysis of the Diagnostic Accuracy of Mobile-Linked Point-of-Care Diagnostics in Sub-Saharan Africa

Abstract: Mobile health devices are emerging applications that could help deliver point-of-care (POC) diagnosis, particularly in settings with limited laboratory infrastructure, such as Sub-Saharan Africa (SSA). The advent of Severe acute respiratory syndrome coronavirus 2 has resulted in an increased deployment and use of mHealth-linked POC diagnostics in SSA. We performed a systematic review and meta-analysis to evaluate the accuracy of mobile-linked point-of-care diagnostics in SSA. Our systematic review and meta-ana… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 50 publications
(81 reference statements)
0
11
0
Order By: Relevance
“…However, digital interventions have significantly improved healthcare services delivery and uptake for other infectious diseases like HIV [ 130 ]. New digital tools like smartphone-based diagnostics are cost-effective for rapid diagnostics in point-of-care testing and could enable real-time remote patient monitoring [ 131 , 132 ]. Thus, the roles of digital interventions in decentralizing and expanding healthcare could be tailored for efficient use in TB care and should be further researched.…”
Section: Discussionmentioning
confidence: 99%
“…However, digital interventions have significantly improved healthcare services delivery and uptake for other infectious diseases like HIV [ 130 ]. New digital tools like smartphone-based diagnostics are cost-effective for rapid diagnostics in point-of-care testing and could enable real-time remote patient monitoring [ 131 , 132 ]. Thus, the roles of digital interventions in decentralizing and expanding healthcare could be tailored for efficient use in TB care and should be further researched.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies found gaps in or sparse or fragmented research on mHealth approaches in SSA for a number of aspects of healthcare such as maternal health, pneumonia, antenatal care, malaria, neurology, hypertension, and obesity. 83 , 38 , 41 , 47 , 48 , 45 , 43 In Europe, findings also reported gaps or limited and fragmented research on several mHealth approaches such as COPDs, obesity, maternal and child health, vaccination programs, and genetics. 58 , 45 , 62 , 63 , 64 Research should be carried out to address these and other existing gaps.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, offering praziquantel in health facilities, including mother and child health care units, by medical personnel [31] and using a test-and-treat strategy instead of preventive chemotherapy without prior diagnosis might increase compliance among adults. However, to date, no sensitive and specific test for S. haematobium detection at the point-of-care exists, presenting a considerable challenge for low-prevalence settings where most people are only slightly infected [32][33][34][35][36]. The development of a highly sensitive and specific test that is affordable and simple and can also be used in health facilities in low-prevalence areas is an urgent need when moving towards interruption of transmission and post-elimination surveillance [37][38][39][40].…”
Section: Discussionmentioning
confidence: 99%